Axiological Features of the Concept CHARM / CHARIVNIST in the English and Ukrainian Languages (Contrastive Aspect) - Томчаковська, Юлія Олегівна; Томчаковська, Ю. О.; Томчаковская, Юлия Олеговна; Tomchakovska, Yuliia О. (Pereiaslav : Hryhorii Skovoroda University, 2018)
The article is devoted to the study of the linguo-cultural concept CHARM / CHARIVNIST in the English and Ukrainian languages. The aim of the work is to identify axiological characteristics of the CHARM / CHARIVNIST concept in English and Ukrainian Internet discourses on the basis of the text-recommendations “How to be Charming” / “Yak staty charivnoyu”, etc. The object of the research is concept CHARM / CHARIVNIST as an aesthetic component of the English and Ukrainian world images; the subject – similarity, difference and contrast in the ways of verbalization of concept CHARM / CHARIVNIST in the English and Ukrainian languages and peculiarities of the discourse realization of the given concept in corresponding linguocultures. Internal and external characteristics of the formation of the image of the CHARMING PERSON have been singled out. Internal features are semantic indicators of the concept CHARM / CHARIVNIST. External features are physical indicators of the concept and include mimic, eye contact, voice and touching features. For English-speaking recipients, such axiological feature as SELF-DEVELOPMENT or DEVELOPMENT OF PERSONALITY is important, which is foregrounded through its components: self-esteem, self-confidence, self-control, “simply-be-yourself” that appear first of all in the body language, for example, FACE (satisfaction, expressive), SMILE (genuine, big, friendly, sincerely), EYE CONTACT (direct), TOUCHING (light), HANDSHAKE (firm), and VOICE (boldness, confident, gentle, peaceful, direct). The following axiological features of the concept of CHARIVNIST in the Ukrainian texts-recommendations have been singled out: sincerity, cheerfulness, originality, with physical characteristics (eyes, voice, smile) serving as "external indicators of the charming inner world", for example, eyes as a mirror of the soul, a smile as a generator of positive fluids, etc. It has been proved that the discoursive feature of SELF-DEVELOPMENT of the English concept CHARM is contrasting. It has been established that such discoursive feature of the Ukrainian concept CHARIVNIST as ORIGINALITY is contrasting, and the discoursive features CONFIDENCE and VPEVNENIST are integral to the two concepts.

Стаття присвячена дослідженню лінгвокультурного концепту CHARM / ЧАРІВНІСТЬ в англійській та українській мовах. Мета роботи – виявити ціннісні характеристики концепту CHARM / ЧАРІВНІСТЬ в англомовному та україномовному Інтернет-дискурсах на матеріалі текстів-рекомендацій «How to be Charming» / «Як бути чарівним» та ін. Об’єктом дослідження є концепт CHARM / ЧАРІВНІСТЬ як естетичний компонент англомовної та україномовної картин світу; предметом – подібності, відмінності та контрасти в способах вербалізації концепту CHARM / ЧАРІВНІСТЬ в англійській та українській мовах і специфіка дискурсивного втілення даного концепту у відповідних лінгвокультурах. Проведений аналіз уможливив виділення внутрішніх і зовнішніх ознак формування іміджу CHARMING PERSON / ЧАРІВНА ЛЮДИНА. Внутрішні ціннісні ознаки є змістовними індикаторами концепту CHARM / ЧАРІВНІСТЬ. Зовнішні ціннісні ознаки є фізичними індикаторами концепту і включають мімічні, окулесичні, фонаційні та гаптичні ознаки. Для англомовних реципієнтів важливою є така ціннісна ознака, як SELFDEVELOPMENT або DEVELOPMENT OF PERSONALITY / САМОРОЗВИТОК, яка актуалізується через її складові: self-esteem/самоповага, selfconfidence / впевненість у собі, self-control / володіння, самовладання, «simply-be–yourself» / «просто-будь-собою», що виявляються, у першу чергу, у мові тіла (BODY LANGUAGE), наприклад, FACE (satisfaction, expressive), SMILE (genuine, big, friendly, sincerely), EYECONTACT (directly), TOUCHING (light), HANDSHAKE (firm), а також VOICE (boldness, confident, gentle, peaceful, direct). Виокремлено такі аксіологічні ознаки концепту ЧАРІВНІСТЬ в україномовних текстах-рекомендаціях: душевність, щирість («широка душа», «душа компанії»), життєрадісність («центр тяжіння компанії»), своєрідність («родзинка»), при цьому фізичні характеристики (очі, голос, усмішка) слугують «зовнішніми індикаторами чарівного внутрішнього світу», наприклад, очі як дзеркало душі, усмішка як генератор позитивних флюїдів тощо. Доведено, що дискурсивна ознака SELF-DEVELOPMENT англомовного концепту CHARM є контрастною. Установлено, що така дискурсивна ознака українського концепту ЧАРІВНІСТЬ, як СВОЄРІДНІСТЬ є контрастною, а дискурсивні ознаки CONFIDENCE і ВПЕВНЕНІСТЬ є інтегральними для двох концептів.

Статья посвящена исследованию лингвокультурного концепта CHARM / ЧАРІВНІСТЬ в английском и украинском языках. Цель работы – выявить ценностные характеристики концепта CHARM / ЧАРІВНІСТЬ в англоязычном и украиноязычном Интернет-дискурсах на материале текстов-рекомендаций «How to be Charming» / «Як бути чарівним» и др. Объектом исследования является концепт CHARM / ЧАРІВНІСТЬ как эстетический компонент англоязычной и украиноязычной картин мира; предметом – сходства, различия и контрасты в способах вербализации концепта CHARM / ЧАРІВНІСТЬ в английском и украинском языках и специфика дискурсивного воплощения данного концепта в соответствующих лингвокультурах. Проведенный анализ позволил выделить внутренние и внешние признаки формирования имиджа CHARMING PERSON / ЧАРІВНА ЛЮДИНА. Внутренние ценностные признаки являются содержательными индикаторами концепта CHARM / ЧАРІВНІСТЬ. Внешние ценностные признаки являются физическими индикаторами концепта и включают мимические, окулесические, фонационные и гаптические признаки. Для англоязычных реципиентов важна такая ценностная составляющая, как SELF-DEVELOPMENT или DEVELOPMENT OF PERSONALITY / САМОРАЗВИТИЕ, которая актуализируется через ее составляющие: self-esteem / самоуважение, self-confidence / уверенность в себе, self-control / самообладание, «simplybe-yourself» / «просто-будь-собой, выявляемых в первую очередь, в языке тела (BODY LANGUAGE), например, FACE (satisfaction, expressive), SMILE (genuine, big, friendly, sincerely), EYE CONTACT (directly), TOUCHING (light), HANDSHAKE (firm), а также VOICE (boldness, confident, gentle, peaceful, direct). Выделены такие аксиологические признаки концепта ЧАРІВНІСТЬ в украиноязычных текстах-рекомендациях: душевность, искренность («широка душа», «душа компанії»), жизнерадостность («центр тяжіння компанії»), своеобразие («родзинка»), при этом физические характеристики (глаза, голос, улыбка) служат «внешними индикаторами обаятельного внутреннего мира», например, глаза как зеркало души, улыбка как генератор положительных флюидов и тому подобное. Доказано, что дискурсивный признак SELFDEVELOPMENT англоязычного концепта CHARM является контрастным. Установлено, что такой дискурсивный признак украинского концепта ЧАРІВНІСТЬ, как СВОЕОБРАЗИЕ является контрастным, а дискурсивные признаки CONFIDENCE и УВЕРЕННОСТЬ являются интегральными для двух концептов.
Tomchakovska Yu. Axiological Features of the Concept CHARM / CHARIVNIST in the English and Ukrainian Languages (Contrastive Aspect) / Yu. Tomchakovska // Psycholinguistics. - Vol. 24. - Issue 2. - Pereiaslav : Hryhorii Skovoroda University, 2018. - Р. 306-320.
Keywords: concept; axiological features; Internet discourse; charm; charivnist; концепт; ціннісні ознаки; Інтернет-дискурс; чарівність; концепт; ценностные признаки; Интернет-дискурс; charm; очарование; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics